Investigating potential anti-proliferative activity of different statins against five cancer cell lines - Gauhar Sarbassova; Nurbek Nurlan; Basim Raddam Al shammari; Nidhish Francis; Mohammed Alshammari; Mohamad Aljofan (Elsevier, 2023)
Statins have been reported to have potential anti-proliferative effects through an unknown mechanism. This study aims to investigate the anti-proliferative activities of five statins, including simvastatin, rosuvastatin, fluvastatin, atorvastatin, and pravastatin, against five different cancer cell lines; cervical epithelial carcinoma DoTc2 4510, malignant melanoma A-375, muscle Ewing's sarcoma A-673, hepatocellular carcinoma HUH-7, as well as breast cancer cells MCF-7. At 100 µM, simvastatin and atorvastatin significantly inhibited 70% of cellular proliferation. At the same concentration, rosuvastatin and fluvastatin showed about 50% of inhibition only in A-375 and A-673 cancer cells in a time- and dose-dependent manner. Of all the statin drugs used, pravastatin had the least inhibitory effect on all the cancer cell lines. Western Blot analysis showed a decrease in mTOR level, and the expression of p53 tumour suppression and BCL-2 proteins was relatively elevated compared to the untreated cells. Simvastatin and atorvastatin may inhibit cellular proliferation via BCL-2/p53, Bax/Bak, and PI3K/Akt/mTOR signalling pathways. This is the first research to evaluate the anti-cancer effects of simvastatin, rosuvastatin, fluvastatin, atorvastatin, and pravastatin against five different cell lines from distinct origins and provided a relevant comparison of their efficacies for their anti-proliferative activity.